3D Relief Cutting Process Using 2D Image Luminosity Grayscaling on The G-Weike WK1212 CNC Router Machine - Dewa Kusuma Wijaya; Pramudi Arsiwi (OPSI, 2021)
This study implements the image litophane processing method to convert 2D images into 3D designs using image luminosity grayscaling techniques, so that the design process as input data for CNC router machining operations can be carried out quickly to support rapid prototyping technology. Furthermore, this research will process the 3D design into a 3D engraving object with a relief cutting process using a G-Weike WK1212 CNC router machine. Using the image luminosity grascaling technique, the color composition value is obtained to change the grayscale color image by 33% red, 59% green and 11% blue with a luminosity value of 35% or 89 from the range of luminosity grayscale levels 0 - 255. These results are further increased by 50% to 172 or 67% of the range of grayscale luminosity levels L[0, 255] so that it will be at the ideal luminosity value for the relief cutting process. Using a luminosity value of 172 from a grayscale image, the actual depth value is 1.82mm from a total depth of 3mm, which of course the relief pattern will look good.